Legal Position Analysis of Shareholders Who Did Not Make Full Deposit in Limited Liability Company Case Study of PT Agen Gas in Central Java - Raihan Jaisy Kamal; Sekartaji Puspaningdyah Hapsari; Nyulistiowati Suryanti; Deviana Yuanitasari (Jurnal Restorasi : Hukum dan Politik, 2024)
There is a clear boundary between the corporation and its owners, which is not the same as shareholders. Capital that can be approved, placed, or paid up is one of the components of a company's articles of association. Article 33 paragraph (1) of the Limited Liability Company Law also stipulates that a full deposit of 25% of the authorized capital is required. To emphasize common legal occurrences, it is known that shareholders often fail to fulfill their responsibilities in providing the working capital required by the deed of incorporation at the beginning of the company's existence. In this study, we looked at issues from closed cases that we collected from a number of gas agency LLCs in Central Java. Examine the rights of shareholders, procedures for proving ownership, and the legal position of shareholders who do not contribute all their capital. Writing systematically based on an analytical-critical approach and the nature of literature research is the research method used. The findings of this study also make it clear that shareholders who do not pay the full issued capital according to the agreement are in default in connection with the agreement to form a limited liability company, as stated in Article 33 of the PT Law Number 40 of 2007 concerning Limited Liability Companies. Limited. The people involved in this lawsuit have all been officially recognized as shareholders, which means that their names are now considered inseparable. Therefore, shareholders must acquire and maintain their rights as shareholders.